LITERATURE IN ENGLISH STUDIES: A THEORY OF HOW TEACHERS AND STUDENTS WITH THE SUBJECT - Murtdha Ayad Mohammed Dawood (European Journal of Humanities and Educational Advancements, 2022)
There is ambiguity in Singapore’s Literature curriculum. A new study on the topic has highlighted this ambiguity and offered ways to rethink it in light of the contemporary environment and the influence of globalization (Choo 2004; Holden 2000; Choo, 2011; Holden, 2000; Choo, 2011; Poon, 2007). Data from Singapore’s secondary schools examined literature’s role in today’s political, economic, social, and educational context. Using in-depth interpretative case studies done at five Singaporean school sites, this research examines students’ viewpoints and delivers findings from in-depth interpretive case studies. Focus group interviews, written protocols, and document analysis have been used to gather data. The negligible impact of local literature on literature studies, the low status of literature, and the lack of interest in literature as a course of study have led to the formulation of four basic premises that underpin the idea of how students in Singapore secondary schools approach literature. Theoretical, policy, and practice benefit from the findings that student’ empirical research yields.